Between friend and foe: drivers and patterns of dyadic relationship framing in policy network - Lee, Junesoo; Lee, Jeongyoon (International Journal of Public Sector Management, 2024)
Purpose This article aims to explore (1) specific frames of dyadic relationship in policy network beyond a simplistic dichotomy of “friend or foe” and (2) the multi-dimensional drivers behind the framing patterns. Design/methodology/approach To that end, the interviews with the key actors in a nuclear energy policy network in South Korea were conducted, and their relationships in terms of three dimensions were analyzed: belief accordance, communication frequency and resource symmetry. Findings As a result, 12 relationships that can occur in the policy networks were identified: helping, collaborating, cooperating, unconcerned, stabilizing, observing, pushing, confronting, challenging, ignoring, watching and avoiding. These 12 frames were observed in various in-/congruent patterns between network actors. Originality/value The findings provide theoretical and practical implications on why and how the network actors may assess one another through the 12 discrete frames, which are drawn from the three dimensional drivers of belief accordance, communication frequency and resource symmetry.